A novel approach to incorporating previous fatigue damage into a failure model for short-fibre reinforced plastics. (April 2022) - Witzgall, Christian; Giolda, Jessica; Wartzack, Sandro
Highlights: Prior fatigue damage strongly influences composites' impact behaviour. Material data from virgin specimen not sufficient for prediction of failure. Consideration of fatigue damage and strain rate in composite failure model. Prediction quality reasonably good for specimen simulations. Abstract: This paper describes how previous material damage due to cyclic loading can influence the failure properties of short-fibre reinforced thermoplastics under crash conditions. To enable these effects to be incorporated into numerical crash simulations, we present a mathematical failure model that takes fatigue damage into account. We perform an experimental study on the thermoplastic PBT GF30: We initially characterize the material under cyclic loading conditions. Subsequently, the behaviour of pre-damaged material specimens in highly dynamic loading experiments is compared to that of virgin specimens to determine the loss of strength due to fatigue damage. Based on the aforementioned experimental results, we develop, calibrate and implement an analytical model for use in the commercial software LS-DYNA.